2D Squaraine‐Bridged Covalent Organic Polymers with Promising CO2 Storage and Separation Properties. Issue 3 (21st March 2016) - Huang, Ling; Cao, Gengyu
Abstract: Three hypothetical 2D porous covalent organic polymers, named SQ‐COPs (i. e., SQ‐COP‐1, SQ‐COP‐2 and SQ‐COP‐3), have been proposed via the combination of linear squaraine unit and heterocyclic molecules (H3 B3 O3, H3 B3 N3 and H3 C3 N3 ). By using the first principle methods and grand cannonical Monte Carlo (GCMC) simulations, these SQ‐COPs are predicted to possess big pore sizes (13.8‐15.0 Å), large free volumes (5.07‐10.94 cm 3 g −1 ) and high BET specific surface areas (8585‐8938 m 2 g −1 ), which even exceed those of MOF‐210 and PAF‐1. As is expected, these SQ‐COPs show promising gas storage and separation properties of H2, CH4, N2 and CO2 at ambient conditions. Especially at 298 K and 30 bar, their CO2 uptake reaches 804, 575 and 633 mg/g respectively, significantly higher than those of zeolites. Meanwhile, for separation of binary gas mixtures CO2 /H2, CO2 /CH4, CO2 /N2, and CH4 /H2, SQ‐COPs are comparable with most of COFs and MOFs. These porous SQ‐COPs materials are not only environmental‐friendly (metal‐free), but also promising candidates for CO2 capture. Abstract : Three 2D porous squaraine‐bridged covalent organic polymers (i. e., SQ‐COP‐1, SQ‐COP‐2 and SQ‐COP‐3) are proposed, and the gas (CO2, CH4, N2, and H2 ) adsorption behaviours as well as the separation of their binary mixtures (CO2 /H2, CO2 /CH4, CO2 /N2, and CH4 /H2 ) on these SQ‐COPs are studied via GCMC simulations. These functional SQ‐COPs may not only stimulate the development of squaraine chemistry, but also play important roles in CO2 storage and separation.